CO2 ADSORPTION STUDY ON MONTMORILLONITE SURFACES: SYNTHESIS OF ACID-TREATED MONTMORILLONITE AND SIMULATION OF CO2 ADSORPTION ON MONTMORILLONITE USING THE DENSITY FUNCTIONAL THEORY (DFT) - Nur Asysyifa Mufarrida, Huwaida
Carbon dioxide gas (CO2) emissions continue to increase along with the increasing use of fuel in various sectors. To mitigate this impact, efforts are being made to reduce CO2 emission. This study tested the porous material Montmorillonite for its adsorption ability on CO2. Experimental and simulation methods were conducted in this research. Experiments were carried out to determine changes in the morphology of Montmorillonite when treated with oxalic acid. SEM characterization results show that raw Montmorillonite forms fairly homogeneous aggregates, not much different from acid treated Montmorillonite. In the EDS graph, the ratio of Si/Al in acid-treated Montmorillonite is reduced compared to raw Montmorillonite because the acidification process causes retention of Si and Al. The simulation software used the Density Functional Theory (DFT) method in the VASP software. This simulation uses GGA (Generalized Gradient Approximation) with the PBE (Perdew Burke Ernzerhof) function for energy exchange correlation. The PAW (projector Augmented Wave) method has a cut-off energy of 520 eV. In the simulation, the CO2 adsorption mechanism in the Montmorillonite system was successfully observed. The angle of CO2 with the Montmorillonite surface decreases from 118,37o to 110,74o. The bandgap energy of the system decreases by 99,1 meV after adsorption, the bandgap energy of Montmorillonite is 5,6361 eV and the bandgap energy of the CO2/Montmorillonite system is 5,5370 eV. The measured adsorption energy was -0,28 eV. The adsorption that occurs is physical adsorption and is an exothermic event.